Putting the substance in substantial evidence: an evidence-based approach to flexible drug regulation - Krebs, Emanuel; Bubela, Tania; McPhail, Melanie; McCabe, Christopher; Regier, Dean A. (Frontiers in Medicine, 2025)
For new drugs or indications, substantial evidence of clinical effectiveness is required for market authorization. In most jurisdictions, substantial evidence is not explicitly defined. Health regulators exercise discretion and are increasingly tolerant of earlier or less mature evidence. To align with flexible evidentiary standards, we argue for the adoption of a principle and, context-based approach to the evidence threshold. Our approach aims to balance the potential benefits and harms of accelerated authorization, low therapeutic value, and safety, based on a value of information (VoI) framework. In our VoI framework, substantial evidence exists when the expected net health value of further research is less than or equal to zero. We operationalize this approach through two case examples that mirror real-time decision factors such as uncertainty, risk preferences and time inputs. As the evidentiary assessment landscape shifts towards flexibility, iterative and clearly defined approaches to risk assessment are warranted. Clarity will stimulate transparency and accountability for both stakeholders and regulators.